Dehydration in older people: A systematic review of the effects of dehydration on health outcomes, healthcare costs and cognitive performance. (July 2021) - Edmonds, Caroline J; Foglia, Enrico; Booth, Paula; Fu, Cynthia H.Y.; Gardner, Mark
Highlights: Mortality rates are associated with dehydration in older people Health outcomes in older people are linked to, and worsened by, dehydration Neurocognitive functioning in older people may be impacted by dehydration Intervention studies should test strategies to reduce dehydration in older adults Abstract: Objective: To systematically examine the effect of dehydration on health outcomes, identify associated financial costs and consider impacts on cognitive performance in older adults. Design: A systematic review of English-language articles via OVID using MEDLINE, PsychINFO, EMBASE, and others, to March 2018. Included studies examined the relationship between hydration status and health, care costs or cognitive outcome. Setting: Cross sectional and cohort data from studies reporting on dehydration in older adults. Participants: Adults aged 60 years and older. Measurements: Independent quality ratings were assessed for all extracted articles. Results: Of 1684 articles screened, 18 papers (N = 33, 707) met inclusion criteria. Participants were recruited from hospital settings, medical long-term care centres and the community dwelling population. Data were synthesised using a narrative summary. Mortality rates were higher in dehydrated patients. Furthermore, health outcomes, including frailty, bradyarrhythmia, transient ischemic attacks, oral health and surgery recovery are linked to and worsened by dehydration. Length of hospital stay, either as a principal or secondary diagnosis, is greater in those with dehydration, compared to those who are euhydrated. Finally, neurocognitive functioning may be impacted by dehydration. There are issues with study design, inconsistency in hydration status measurement and different measures used for outcome assessment. Conclusion: Dehydration in older people is associated with increased mortality, poorer course of illness and increased costs for health services. In addition, there is some, but sparse evidence that dehydration in older people is linked to poorer cognitive performance. Intervention studies should test strategies for reducing dehydration in older adults.